Improving Understanding of Digital Parenting for Fatayat Mothers to Optimize Children's Digital Media Management in Plumpang District, Tuban Regency, East Java: Peningkatan Pemahaman Pengasuhan Digital Bagi Ibu-Ibu Fatayat untuk Optimalisasi Pengelolaan Media Digital Anak di Kecamatan Plumpang, Kabupaten Tuban, Jawa Timur - Puspitasari, Endang; Ni’mah, Roudlotun; Abi Aufa, Ari (Universitas Haji Sumatera Utara, 2025)
The increasing use of digital media among children has created new challenges in parenting, especially regarding the supervision and control of the content accessed. One group that has an important role in parenting is Fatayat mothers, who are expected to be able to control the use of digital media in their children. This Community Service Program aims to improve the understanding of digital parenting among Fatayat mothers in Plumpang District, Tuban Regency, East Java, in an effort to control digital media in children. This Community Service Program (PKM) is implemented through a series of training and counseling that includes an understanding of the positive and negative impacts of digital media, ways to manage the time spent using digital devices, and how to involve children in discussions about digital security and ethics. The expected results of this activity are increased knowledge and skills of mothers in supervising the use of digital media among their children, as well as the creation of a safer digital environment that supports healthy child development. Thus, better digital parenting can support optimal child growth and development in this digital era.